Comparison of Extraction and Non-extraction Orthodontic Treatment using the Objective Grading System - N. Farhadian; AF. Miresmaeili; MK. Soltani (Tehran University of Medical Sciences, 2005)
Statement of Problem: The extraction versus non-extraction debate is almost as old as the advent of orthodontic practice and up to now, this dilemma remains. Recently, the American Board of Orthodontics (ABO) has developed a method by the name of Objective Grading System (OGS) in order to evaluate the results of orthodontic treatment. Aim: The aim of the present study was to evaluate and compare the patients' final occlusion after extraction and non-extraction therapy using the OGS. Materials and Methods: Sixty sex-matched cases with an age range of 15-20 year old were selected and evenly divided into 2 groups as follows: 30 patients were treated by extraction of 4 premolars and 30 received a non-extraction treatment. All patients had class 1 malocclusion before treatment and were well treated with the standard edgewise system in a private clinic. With the aid of an ABO measuring gauge, 8 parameters of occlusion were measured 3 times, each. Reproducibility of the measurements were evaluated by use of the Phi correlation coefficient and the total OGS scores between the two groups were compared using Levene`s test and Student t- test with the significant level at 95%. Results: The mean OSG scores were significantly more negative in the non-extraction group (-6.58  8.63) as compared to the extraction group (-28.65  6.67, p < 0.004). Acceptable occlusion was observed in 73.4% of the extraction and 43.4% of the non-extraction cases. Conclusion: In this study according to the ABO grading system (OGS), the final occlusion of patients treated with extraction seemed more acceptable than non-extracted cases.